DRAINAGE CHANNELS DESIGN AND RESTORATION OF INTER-TIDAL MARSHES - Mark E. Grismer (Lowland Technology International, 2000)
Geomorphologically, inter-tidal salt marshes are vegetated landforms at elevations slightly greater than mean tidal levels that have distributed channels formed under ebb (drainage) tidal flows that widen and deepen in the seaward direction. The drainage channels enable tidal flows to circulate sediments and nutrients through the marsh system during normal tidal events, while depositing sediments during storm or seismic events. This dynamic system encourages considerable biodiversity while simultaneously providing water quality enhancement features that service marsh terrestrial life and estuary marine life. Reservoir creation, limiting sediment supply, sea level rise as well as agricultural and urban development have resultedd in significant loss of inter-tidal marshes and subsequent and adverse impacts on waterfowl, infauna and fisheries. The complex and continuously changing marsh channel hydraulic and sedimentary processes have severely constrained quantitative modeling of marsh systems such that restoration/creation efforts remain an empirical science. The purpose of this paper is to outline current understanding of salt marsh hydrodinamics, sediment accretion processes and subsequent response of marsh vegetation to set the stage for discussion of a marsh restoration/creation effort in San Paolo Bay near San Fransisco, California. Several kilometers of drainage channels were constructed in a 410 ha disturbed salt marsh to restore tidal circulation and vegetation so as to enhance habitat for threatened species (e.g. clapper rail, salt marsh harvest mouse, delta smelt and anadromous fish species). Two distinct drainage channel system ("east" and "west") were installed having similar channel dimensions common to salt marshes in the region, but having design bankfull tidal prism volumes that differed by a factor of two. Following excavation of the channels, main channel tidal flows and sediment loads as well as marsh sediment accretion rates were monitored to assess the relative success of the channel excavation in restoring tidal circulation and vegetation (Salicornia spp.) to the marsh. Annual aerial surveys corroborated with ground-truthing indicated that marsh vegetation coverage rapidly expanded, from 40 to 63% coverage following excavation. However, channel surveys and flow measurement indicated that the "east" channel system tidal prism prior to nearly complete siltation of the channels within three years was only about 1,200 m3, more that an order of magnitudo less than that of the apparently stable "west" channel system. Marsh sediment accretion rates were on the order of 7-8 mm/yr, a rate common to the Pacific coast region that exceeds estimated sea level rise rates of 1-2 mm/yr. East channel network siltation resulted in ponding following storm and spring tidal events and marsh vegetation coverage decreased to 51% of the marsh area and quality of available habitat decreased. These results are considered in terms of the primary inter-tidal marsh factors affecting possible restoration/creation strategies.